Competition Patterns at the EU Internal Energy Markets in Central Europe - Lipták, Marek; Klosová, Anna, 1942-; Jegers, Marc; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
The first part of the thesis concerns describing the main topics concerned when mentioning electroenergetics: peculiarities of electricity and specifics of this commodity as well as liberalization that took place within this sector and new patterns arisen from these changes mainly in terms of business not only in wholesale, but also with effects on retail. It also outlines the economic rationale behind these changes. The second part of the thesis is an empirical analysis of real wholesale market data, demonstrating results of correlation, convergence and cointegration in spot prices of wholesale electricity in particular European countries.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; economics of globalisation and european integration [obor dipl. práce]